An experimental assessment of displacement fluctuations in a 2D granular material subjected to shear. Issue 3 (3rd September 2012) - Richefeu, V.; Combe, G.; Viggiani, G.
Abstract : In a granular material, a macroscopically homogeneous deformation does not correspond to a homogeneous displacement field when looking at the individual grains. The deviation of a grain displacement from the value dictated by the continuum field (referred to as 'fluctuation') is likely to hold valuable information about the characteristic length(s) involved in the grains' rearrangement, which is the principal mechanism of irreversible deformation for granular materials. This paper shows a selection of results from a series of shear tests on a two-dimensional analogue granular material. The route opened by the pioneering work of Radjaï and Roux is followed, and the same framework is used to analyse the experimental data on displacement fluctuations. Digital image correlation has been used to measure and characterise the displacement fluctuations. The analysis of their spatial organisation reveals the emergence of a minimum-length scale; that is, in the order of 10 times the mean particle size.